2016
DOI: 10.1021/jacs.6b03686
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Base-Catalyzed Diboration of Alkynes Using the Unsymmetrical Diborane(4), pinB-BMes2

Abstract: In the absence of transition metal catalysts, the unsymmetrical diborane(4), pinB-BMes2, reacted with alkynes to afford diborylalkenes. The isomer ratio of the products could be controlled via temperature, solvent, and additive(s). A reaction mechanism was proposed on the basis of two isolated intermediates, and this reaction could furthermore be applied to synthesize a luminescent molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 94 publications
(40 reference statements)
4
50
0
Order By: Relevance
“…Thes ubsequent addition of BPh 3 to [7] À resulted in suppression of 1,2-boryl migration, with [8] À detected only in trace amounts (Scheme 6). Thes ubsequent addition of BPh 3 to [7] À resulted in suppression of 1,2-boryl migration, with [8] À detected only in trace amounts (Scheme 6).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…Thes ubsequent addition of BPh 3 to [7] À resulted in suppression of 1,2-boryl migration, with [8] À detected only in trace amounts (Scheme 6). Thes ubsequent addition of BPh 3 to [7] À resulted in suppression of 1,2-boryl migration, with [8] À detected only in trace amounts (Scheme 6).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The coordination of aL ewis base (LB) to diborane (4) compounds,such as B 2 Pin 2 (1), generates an sp 2 Àsp 3 diborane in which the boron-boron bond is polarised, [1] which imparts nucleophilic character to the sp 2 boron atom, thereby enabling the mild generation of af unctional equivalent of {BPin} À . [1,2] This strategy has become ap owerful transitionmetal-free method to borylate organic substrates and generate desirable organoboronate esters.A lkoxides or Nheterocyclic carbenes (NHCs) are the typical LBs employed in the activation of 1, [1][2][3] with the use of carbanions (R À ) having much less precedent, [4][5][6][7][8][9] despite the ability of carbanions to generate amore nucleophilic {BPin} moiety owing to their greater basicity relative to alkoxides and NHCs.Among the limited examples in this area, recent studies have shown that complex A synthesised from 1 and nBuÀMgL (L = bdiketiminato) transfers aboryl anion to boranes to form new unsymmetrical sp 2 Àsp 3 diboranes (Scheme 1a). [10] Indeed, transfer of ab oryl nucleophile to an external electrophile is the dominant reactivity pathway reported for B 2 Pin 2 activated by simple carbanions.…”
mentioning
confidence: 99%
“…[3p, 6] Bis(pinacolato)diborane (B 2 pin 2 ), which is stabilized by pp-pp interactions from four adjacent oxygen atoms,h as been widely used for transition-metal-catalyzed borylations of organic molecules. [8] Thea bsence of heteroatoms at one of the two boron atoms renders this molecule highly electrophilic.Infact, pinBÀBMes 2 reacts with tert-butylisocyanide leading to cleavage of the NCt riple bond, [8] with CO to provide aC O-coordinated boraalkene, [8] with alkynes to form diborylalkenes, [9] with 2,6-dimethylphenylisocyanide to furnish a1 ,2-oxaboretane ring, [10] with pyridine to give C À Hf unctionalized pyridines, [11] and with electrons to afford the corresponding radical anion. [8] Thea bsence of heteroatoms at one of the two boron atoms renders this molecule highly electrophilic.Infact, pinBÀBMes 2 reacts with tert-butylisocyanide leading to cleavage of the NCt riple bond, [8] with CO to provide aC O-coordinated boraalkene, [8] with alkynes to form diborylalkenes, [9] with 2,6-dimethylphenylisocyanide to furnish a1 ,2-oxaboretane ring, [10] with pyridine to give C À Hf unctionalized pyridines, [11] and with electrons to afford the corresponding radical anion.…”
mentioning
confidence: 99%
“…As such, vinylboronic acid derivatives bearing multiple boron moieties with chemoselective reactivity are highly desirable. For example,p hotocatalyzed diborations in the presence of ac atalytic amount of diphenyl disulfide under light irradiation, [7] and diborations employing strongly Lewis acidic, unsymmetrical diborane (pinBBMes 2 ), [8] afford the 1,2-diborylalkenes as amixture of E-and Z-configured products. [6] Recently,m etal-free conditions have been reported.…”
mentioning
confidence: 99%
“…[6] Recently,m etal-free conditions have been reported. For example,p hotocatalyzed diborations in the presence of ac atalytic amount of diphenyl disulfide under light irradiation, [7] and diborations employing strongly Lewis acidic, unsymmetrical diborane (pinBBMes 2 ), [8] afford the 1,2-diborylalkenes as amixture of E-and Z-configured products.…”
mentioning
confidence: 99%